Research design qualitative, quantitative, and mixed methods approaches - Creswell, John w.; Creswell, J. David (SAGE Publications, Inc, 2018)
This best-selling text pioneered the comparison of qualitative, quantitative, and mixed method research design. For all three approaches, John W. Creswell and new co-author J. David Creswell include a preliminary consideration of philosophical assumptions, key elements of the research process, a review of the literature, an assessment of the use of theory in research applications, and reflections about the importance of writing and ethics in scholarly inquiry